The impact of infection risk communication format on tourism travel intentions during COVID-19. (March 2023) - Savadori, Lucia; Tokarchuk, Oksana; Pizzato, Massimo; Pighin, Stefania
Abstract: Perceived risks and safety concerns are strong predictors of travel intentions. This research examines the effectiveness of the COVID-19 infection rate presentation format in changing respondents' risk perceptions and travel intentions to a COVID-19-affected destination. In two experimental studies conducted during the COVID-19 pandemic, participants (N = 1219) received information on infection rates in one of four mathematically equivalent formats: raw numbers, percentages, N-in-NX ratio, and 1-in-X ratio. Three distinct components of risk perception were measured: affective, analytical, and experiential. Results show that the infection rate presented using percentages increased the intention to travel compared to that presented using an N-in-NX ratio and raw numbers. Moreover, the infection rate presented using a 1-in-X ratio decreased the intention to travel compared to that presented using an N-in-NX ratio and percentages. These findings are in line with two apparently inconsistent phenomena: the ratio bias, according to which ratios with larger numerators induce a higher perceived infection risk than ratios with smaller ones, and the 1-in-X effect, according to which ratios with "1" at the numerator induce a higher perceived infection risk than ratios with other numbers at the numerator. Additionally, the effect of numerical formats on travel intentions was fully mediated by affective and analytical risk perceptions but only partially by experiential risk perceptions. Overall, the findings show the importance of the format used to present infection rates on changing individuals' travel intentions.